2011
DOI: 10.1292/jvms.10-0254
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Viral Diarrhea Virus (BVDV) Infection in Relation to Fertility in Heifers

Abstract: ABSTRACT. In this study, blood serum and leukocyte samples were collected from 400 Holstein heifers, all of which appeared to be healthy. Antibodies (Ab) against bovine viral diarrhea virus (BVDV) were detected in 57 serum samples, and BVDV antigen (Ag) was detected in 38 leukocyte samples. There were statistically important differences between the average first insemination ages (FIT) of the BVDV (Ag-/Ab+) heifers (p<0.0001) (pregnant p<0.05, nonpregnant p<0.0001) and BVDV (Ag-/Ab-) heifers. The average conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
(41 reference statements)
0
6
0
3
Order By: Relevance
“…Pestiviruses infect sheep, cattle and pigs, and cause significant economic losses worldwide. Border disease virus (BDV) belongs to the genus Pestivirus within the family Flaviviridae (Krametter-Froetscher et al, 2007;Kale et al, 2011). Border disease is a congenital viral disease of sheep and goats which was first reported in 1959 in the Border region of Wales and England (Hughes et al, 1959).…”
Section: Introductionmentioning
confidence: 99%
“…Pestiviruses infect sheep, cattle and pigs, and cause significant economic losses worldwide. Border disease virus (BDV) belongs to the genus Pestivirus within the family Flaviviridae (Krametter-Froetscher et al, 2007;Kale et al, 2011). Border disease is a congenital viral disease of sheep and goats which was first reported in 1959 in the Border region of Wales and England (Hughes et al, 1959).…”
Section: Introductionmentioning
confidence: 99%
“…Pestiviruses infect sheep, cattle, and pigs, and cause significant economic losses worldwide [1,2]. Border disease virus (BDV) belongs to the genus Pestivirus within the family Flaviviridae.…”
Section: Introductionmentioning
confidence: 99%
“…Detrimental effects of BVDV infection on fertility were also reported in field studies, in which poor conception rates, early embryonic losses, and pregnancy losses were detected. [135][136][137][138] In contrast, heifers exposed to PI calves for 220 days beginning at 50 days prior to the breeding season had the same pregnancy rates as unchallenged control heifers, resulting from development of protective immune responses prior to breeding. 139 Highlighting the benefits of a controlled breeding season, this study demonstrated that BVDV infections can be self-limiting in certain herds, when all animals are protected from BVDV during gestation and PI calves are not born.…”
Section: Postnatal Infections In Immunocompetent Cattlementioning
confidence: 99%